LOCAL CULTURE IN A DISRUPTIVE WORLD - Sandra Dewi Dahlan (UIN Alauddin Makassar, 2023)
This study aimed to describe the implementing digitizing folklore in the English Drama Course to the students of English and Literature Department. In addition, to evaluate the student responses to the project as part of cultural preservation efforts. This study used mixed methods to collect qualitative and quantitative data. The population of the research were fourth semester students of class AG 2/3 of English and Literature Department of UIN Alauddin Makassar. The object was the English Drama Course by applying the